An Analysis of Idiomatic Expression in Aladdin (2019) Film Soundtrack Lyrics - Rahmadina, Fadhila; Nasir, Muhammad Alim Akbar (Ilmu Budaya: Jurnal Bahasa, Sastra, Seni, dan Budaya, 2024)
This research investigated the idiomatic expressions in the song lyrics of the Aladdin (2019) film soundtrack. Aladdin (2019) is a live-action adaptation of the One Thousand and One Night tales, based on Walt Disney's 1992 animated film of the same title. The aim of this study is to identify the types of idioms and meanings in Aladdin (2019) film soundtrack lyrics. This study applied a qualitative approach, drawing on Adam Makkai's theory of idiomatic expression and Geoffrey Leech's seven types of meaning theory. The results showed that 72 idioms have been used throughout the six songs chosen in the soundtrack. The researcher discovered every form of idioms, with tournure idioms being the most common, followed by phrasal verb, pseudo, irreversible binomials, phrasal compound, and incorporating verb. The research discovered that each of the six songs picked has a unique significance. In general, Aladdin portrays timeless themes like self-discovery, love, friendship, and the desire for freedom. Readers will gain a comprehensive understanding of what idioms are, their various types and classification, their usage and function in communication, and how they are processed by the speakers. This research also explores cross-linguistics comparison and their presence in literature and media.